2018
DOI: 10.18203/2320-1770.ijrcog20183789
|View full text |Cite
|
Sign up to set email alerts
|

Maternal complications in twin pregnancy; recent trends: a study at a tertiary care referral institute in Northern India

Abstract: Background: This study aims to determine the maternal complications in twin pregnancy in North Indian population at tertiary institute.Methods: This was a retrospective cohort review of multiple pregnancies after 20 weeks gestation at a tertiary teaching hospital (2011-2015). Maternal data was collected from the labor room delivery data entry register and patient’s admission file. Patients with diabetes mellitus and chronic hypertension were excluded from the study.Results: Out of 19539 births during this peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…[22][23][24] Our study reports 66% primigravida and 34% multigravida which is contrary to already published study in which 84.2% were multigravida another study reported 45.7% primigravida and 54.3% multigravida. 25,26 Studies reported preterm delivery in 60% and 67% of twin pregnancies and few other studies reported even lower 38%29 and 44%30, which is in line with our study. Studies have reported cesarean section (LSCS) in 68%, 49% and 45% where as our study reports it as 92%.…”
Section: Discussionsupporting
confidence: 92%
“…[22][23][24] Our study reports 66% primigravida and 34% multigravida which is contrary to already published study in which 84.2% were multigravida another study reported 45.7% primigravida and 54.3% multigravida. 25,26 Studies reported preterm delivery in 60% and 67% of twin pregnancies and few other studies reported even lower 38%29 and 44%30, which is in line with our study. Studies have reported cesarean section (LSCS) in 68%, 49% and 45% where as our study reports it as 92%.…”
Section: Discussionsupporting
confidence: 92%
“…Dubey et al had 45.7% primigravida and 54.3% multigravida. 6,8 Mean gestational age at delivery in our study was 34.53 weeks which was comparable with Erdemoghu et al and Yuel et al 9,10 Hypertensive disorder in pregnancy (40.90%) was the most frequent complication associated with twin pregnancy in our study. 24 to 30 % was noticed by other workers.…”
Section: Discussionsupporting
confidence: 89%
“…Maximum age group with twin pregnancy was between 20 -29 years (56.06%) in our study whereas 86.9% and 81% in Dubey et al and Tomar et al respectively. 6,7 This shows that maximum women who sought ART treatment are below 30 years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Multiple birth babies have a two times higher chance of having birth defects such as neural tube defects, cardiac defects and gastrointestinal defects, compared to single birth babies. 17…”
Section: Congenital Defectsmentioning
confidence: 99%